Peran Akuntansi Manajemen Berbasis Teknologi dalam Pengambilan Keputusan Bisnis: Tinjauan Literatur - Veronika Christine Mevelia; Diah Indri Anggriyanti; Cholis Hidayati (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The development of digital technology has driven fundamental changes in management accounting practices, which no longer serve merely as internal recording tools but have transformed into strategic support systems for business decision-making. This article aims to systematically examine the role of technology-based management accounting in supporting decisions at the strategic, operational, and tactical levels. This study employs a Systematic Literature Review (SLR) method on 20 relevant scientific articles published between 2021 and 2025. The findings indicate that the integration of technologies such as ERP, cloud accounting, artificial intelligence (AI), and big data can enhance the accuracy, speed, and efficiency of managerial decision-making. Additionally, it was found that the implementation of technology significantly impacts operational efficiency and a company's competitiveness. However, the success of implementing technology-based management accounting systems heavily depends on organizational readiness, human resource competencies, as well as supportive work structures and cultures. This article also identifies gaps in the literature, particularly in the context of SMEs, which present important opportunities for future research.